HW05-solutions - husain (aih243) HW05 Gilbert (56215) 1...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: husain (aih243) HW05 Gilbert (56215) 1 This print-out should have 25 questions. Multiple-choice questions may continue on the next column or page find all choices before answering. 001 10.0 points Determine f ( x ) when f ( x ) = 2 sin3 x + 3 cos 2 x . 1. f ( x ) = 6(cos 3 x + sin2 x ) 2. f ( x ) =- 6(sin2 x + cos 3 x ) 3. f ( x ) = 2 cos 3 x + 3 cos 2 x 4. f ( x ) = 6(cos 3 x- sin2 x ) correct 5. f ( x ) = 2 cos 3 x- 3 sin2 x 6. f ( x ) =- (3 sin2 x + 2 cos3 x ) Explanation: Since d dx sin x = cos x , d dx cos x =- sin x , the Chain Rule ensures that f ( x ) = 6(cos 3 x- sin2 x ) . 002 10.0 points Find f ( x ) when f ( x ) = parenleftBig x- 2 x + 1 parenrightBig 2 . 1. f ( x ) =- 6( x + 2) ( x- 1) 3 2. f ( x ) =- 4( x- 2) ( x + 1) 3 3. f ( x ) = 6( x + 1) ( x- 1) 3 4. f ( x ) =- 4( x + 1) ( x- 1) 3 5. f ( x ) = 4( x- 1) ( x + 1) 3 6. f ( x ) = 6( x- 2) ( x + 1) 3 correct Explanation: By the Chain and Quotient Rules, f ( x ) = 2 parenleftBig x- 2 x + 1 parenrightBig ( x + 1)- ( x- 2) ( x + 1) 2 . Consequently, f ( x ) = 6( x- 2) ( x + 1) 3 . 003 10.0 points Determine f ( x ) when f ( x ) = x- 1 x 2- 2 . 1. f ( x ) = 2- x ( x 2- 2) 3 / 2 2. f ( x ) = x- 2 ( x 2- 2) 3 / 2 correct 3. f ( x ) = 2 + x ( x 2- 2) 1 / 2 4. f ( x ) = x- 2 ( x 2- 2) 1 / 2 5. f ( x ) = 2 + x ( x 2- 2) 3 / 2 6. f ( x ) = 2- x ( x 2- 2) 1 / 2 Explanation: By the Product and Chain Rules, f ( x ) = 1 ( x 2- 2) 1 / 2- 2 x ( x- 1) 2( x 2- 2) 3 / 2 = ( x 2- 2)- x ( x- 1) ( x 2- 2) 3 / 2 . husain (aih243) HW05 Gilbert (56215) 2 Consequently, f ( x ) = x- 2 ( x 2- 2) 3 / 2 . (Note: the Quotient Rule could have been used, but its simpler to use the Product Rule.) keywords: derivative, square root, chain rule, product rule 004 10.0 points Determine the derivative of f ( x ) = ( x- 3) x- 2 . 1. f ( x ) = 3 x + 7 x- 2 2. f ( x ) = 3 x + 7 2( x- 2) 3. f ( x ) = 3 x- 7 2 x- 2 correct 4. f ( x ) = 3 x + 7 x- 2 5. f ( x ) = 3 x- 7 x- 2 6. f ( x ) = 3 x- 7 2( x- 2) Explanation: By the Product and Chain Rules, f ( x ) = 1 2 x- 2 ( x- 3) + x- 2 = x- 3 + 2( x- 2) 2 x- 2 . Consequently, f ( x ) = 3 x- 7 2 x- 2 . keywords: Product Rule, Chain Rule, Power Rule, square root function, 005 10.0 points Find the first derivative of f when f ( x ) = 2 cos2 x- sin 2 x . 1. f ( x ) =- 10 sin2 x 2. f ( x ) =- 5 cos 2 x 3. f ( x ) =- 5 sin2 x correct 4. f ( x ) = 10 sin2 x 5. f ( x ) = 5 sin2 x 6. f ( x ) =- 10 cos2 x Explanation: By the Chain Rule we see that f ( x ) =- 4 sin2 x- 2 sin x cos x ....
View Full Document

Page1 / 12

HW05-solutions - husain (aih243) HW05 Gilbert (56215) 1...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online